SUPPLY CHAINS OF MINERAL RAW MATERIALS AND MONTANISTIC TOURISM - Schejbal, Ctirad (GeoScience Engineering, 2017)
Supply chains in mineral raw material industry take different forms depending on the requirements, the placement of resources and points of consumption and the nature of the geological, morphological and botanical landscape type. Hitherto, in the context of montanistic tourism paid attention primarily to the objects associated with the exploration and exploitation of mineral resources accumulations. Professionally and touristically can be interesting processes of transport of mineral raw materials and products of their processing. Therefore, in during the selection, development and implementation of montanistic tourism products will be useful to focus on these parts of the supply chain, especially if they are implemented in areas with high levels of geodiversity and biodiversity.